Caracterização biofísica dos 5000 m crol em águas abertas - Tiago da Silva Oliveira (2018)
Understanding the biophysical determinants of open water swimming is fundamental to enhance performance and achieve high-standard levels in competitive swimming. Scientific research in open water is taking its first steps and is still scarce, and no studies are known to carry out a biophysical analysis at official distances and environments (5, 7.5 and 10 km). The purpose of this Thesis was to identify and characterize front crawl biophysical performance determinants in 5000 m in open environment, simulating a competitive situation. Seven swimmers, four males and three females, were evaluated in a 5 x 1000 m protocol for the assessment of bioenergetic variables, such as blood lactate concentration ([La-]) and blood glucose, of biomechanical variables, such as stroke rate (SR), velocity (v), stroke length (Sl) and stroke index (SI), and also of ventilatory variables, such as oxygen uptake (V̇O2 kinetics), pulmonary ventilation and respiratory coefficient. In the biomechanical variables we recorded a mean value of the velocity of 1.27 ± 0.07 m∙s-1, during the test, recorded also a mean value 33.8 ± 2.2 cycles.min-1 for stroke rate, 2.27 ± 0.19 m.cycle-1 for stroke length, 7.47 ± 0.49 m2.s-1.cycle-1 for stroke index (SI), while in the bioenergetic variables we recorded a mena value of 2.4 ± 0.9 mmol∙L-1 for [La-] and 86 ± 6 mg.dL-1 for blood glucose. In the ventilatory variables we recorded a mean value of the V̇O2absolute of 2.61 ± 0.61 L·min-1, a mean value of 72.6 ± 19.4 L·min-1 for pulmonar ventilation and, in respiratory coefficient, we recorded a mean value of 0.99 ± 0.04, with energy expenditure and energy cost ranged around 637 ± 54 kJ and 0.6 ± 0.05 kJ∙m-1 with the aerobic pathway accounting for ~95.6%. The results suggest that in 5000 m open water swimming, the aerobic energy contribution plays a fundamental role in energy demand swimmers and there is also a physiological balance along with a biomechanical fit.